CHILDREN'S LEARNING MEDIA TO RECOGNIZE ANIMALS USING MARKER BASED TRACKING AUGMENTED REALITY TECHNOLOGY BASED ON ANDROID - Aji Supriyanto; Budi Hartono; Ardiyan Roosenda Setyadi; Theresia Dwiati Wismarini (Informatika, Universitas Jenderal Soedirman, 2022)
Augmented reality (AR) is a technology that virtualizes 2-dimensional (2D) image objects to produce 3-dimensional (3D) objects in real time on a monitor or smartphone screen. AR in order to display a 3-dimensional object requires a marker. Markers are generally in the form of images or images. In AR that has been made the application can detect the marker. AR implementation can now be found in various fields, one of which is the field of education for learning, especially for children. In this study, AR was developed to be applied as a learning medium by introducing the behavior, characteristics or features of animals viewed through devices such as smartphones or tabs. The types of animals used in the experiment were land, water, and air animals so that the children could imagine the shape of the animal in 3 dimensions and gain knowledge about the characteristics of the animal through the description of the sound of the animal. The markers that will be detected by the system are cartoon images of animals that match their 3-dimensional shape, so that application users can enjoy learning. This application was built using Unity 3D with the development stages using the waterfall model. The result is that besides being able to display 3-dimensional visuals, it can also display videos like videos that are equipped with sounds that show the characteristics or features of the animal.